2011
DOI: 10.3233/nre-2011-0664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endurance exercise training on the expression of GFAP, S100B, and NSE in the striatum of chronic/progressive mouse model of Parkinson's disease

Abstract: Goals and Objectives: Parkinson's disease (PD) is one of the most common neurodegenerative diseases in elderly. Glial fibrillary acidic protein (GFAP), calcium-binding protein (S100B), and neuron-specific enolase (NSE) are brain damage markers. The main goal of this study is to investigate the expression of these markers in the striatum (ST) of chronic/progressive mouse model of PD, and to study the effect of endurance exercise training on the expression of those markers. Materials and Methods: In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 3 publications
1
9
1
1
Order By: Relevance
“… 52 reported a negative correlation between serum S100β levels and total antioxidant status ( r = −0.64). Moreover, Al-Jarrah and Jamous 53 previously reported that treadmill exercise training decreased S100β and NSE expression in a Parkinson's disease mouse model, supporting the results of this study. In addition, even though serum S100β and NSE levels are blood biomarkers for BBB disruption and a BBB permeability increase, 21 , 54 future studies analyzing circulating tight junction proteins and matrix metalloproteinases may more specifically reflect BBB function because S100β is expressed in various peripheral tissues, including skeletal muscle, and NSE reflects brain damage.…”
Section: Discussionsupporting
confidence: 89%
“… 52 reported a negative correlation between serum S100β levels and total antioxidant status ( r = −0.64). Moreover, Al-Jarrah and Jamous 53 previously reported that treadmill exercise training decreased S100β and NSE expression in a Parkinson's disease mouse model, supporting the results of this study. In addition, even though serum S100β and NSE levels are blood biomarkers for BBB disruption and a BBB permeability increase, 21 , 54 future studies analyzing circulating tight junction proteins and matrix metalloproteinases may more specifically reflect BBB function because S100β is expressed in various peripheral tissues, including skeletal muscle, and NSE reflects brain damage.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our hypothesis is that the physical exercise increased the plasma levels of brain-derived neurotrophic factor, which plays an important role in neuroplasticity and participates in neural transmission and modulation as well as cell proliferation and neurogenesis, improving cognitive function [ 38 , 39 , 40 , 41 ]. Exercise can also decrease the expression of the enzyme neuron-specific enolase and the protein S100B that may worsen cognition [ 42 ]; the assessment of these variables could be important to explain our results and will be our focus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Jarrah et al 81 found that endurance exercise training could promote angiogenesis in a mouse model of PD. In addition, they found this training could decrease the expression of brain damage markers in the striatum, 82 possibly by decreasing the level of neuronal nitric oxide. 83 Strong evidence showed that long-term aerobic exercise could help functional motor and limbic circuits' reorganization in a rat model of PD 84 and that longer-duration vibration training could significantly increase the number of nigrostriatal dopaminergic neurons.…”
Section: Neurorestorative Mechanisms Of Neurorehabilitation For Pdmentioning
confidence: 98%